Liangkang Ni on Husserl and Buddhism: a comparative phenomenological analysis - Gutland, Christopher; Liu, Huan (Frontiers in Psychology, 2025)
Over several decades, Liangkang Ni has developed a distinctive perspective on the parallels and divergences between Edmund Husserl’s phenomenology and Buddhism, particularly Yogācāra Buddhism. Despite the significance of his contributions, Ni’s writings remain largely unavailable in English and have thus had limited exposure in Western phenomenological discourse. This article addresses that gap by offering a thematic reconstruction of Ni’s key insights. The first part examines Ni’s reading of Husserl’s own philosophical reflections on Buddhism in relation to phenomenology. The second part explores Ni’s reconstruction of genetic and structural parallels between Husserl’s genetic phenomenology and Yogācāra doctrines such as vijñaptimātra (consciousness-only), ālaya-vijñāna, and manas. The article assumes some familiarity with Husserl and uses his framework as an entry point to introduce Buddhist concepts. Rather than offering new empirical data, the article provides conceptual clarification and theoretical integration aimed at informing contemporary debates in consciousness studies.